Deliver us from Evil: The Effects of Mortality Salience and Reminders of 9/11 on Support for President George W. Bush - Mark J. Landau; Sheldon Solomon; Jeff Greenberg; Florette Cohen; Tom Pyszczynski; Jamie Arndt; Claude H. Miller; Daniel M. Ogilvie; Alison Cook (Personality and Social Psychology Bulletin, 2004)
According to terror management theory, heightened concerns about mortality should intensify the appeal of charismatic leaders. To assess this idea, we investigated how thoughts about death and the 9/11 terrorist attacks influence Americans’ attitudes toward current U.S. President George W. Bush. Study 1 found that reminding people of their own mortality (mortality salience) increased support for Bush and his counterterrorism policies. Study 2 demonstrated that subliminal exposure to 9/11-related stimuli brought death-related thoughts closer to consciousness. Study 3 showed that reminders of both mortality and 9/11 increased support for Bush. In Study 4, mortality salience led participants to become more favorable toward Bush and voting for him in the upcoming election but less favorable toward Presidential candidate John Kerry and voting for him. Discussion focused on the role of terror management processes in allegiance to charismatic leaders and political decision making.
Keywords: terror management theory; terrorism; 9/11; George W. Bush; election politics; charismatic leaders